2015
DOI: 10.1523/jneurosci.3446-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Converging Evidence for the Neuroanatomic Basis of Combinatorial Semantics in the Angular Gyrus

Abstract: Human thought and language rely on the brain's ability to combine conceptual information. This fundamental process supports the construction of complex concepts from basic constituents. For example, both "jacket" and "plaid" can be represented as individual concepts, but they can also be integrated to form the more complex representation "plaid jacket." Although this process is central to the expression and comprehension of language, little is known about its neural basis. Here we present evidence for a neuroa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
191
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(214 citation statements)
references
References 51 publications
22
191
1
Order By: Relevance
“…This hierarchy, as well as the divergence of neural responses observed here, is additionally consistent with previously proposed linguistic hierarchies: low-level regions (A1+) represent phonemes (32,33), syllables (34), and pseudowords (35), while medium-level regions (areas along A1+ to STS) represent sentences (36,37). At the top of the hierarchy, high-level regions (bilateral TPJ, precuneus, and medial prefrontal cortex) can integrate words and sentences into a meaningful, coherent whole narrative (5,15,(38)(39)(40). We found that the regions at the top of the hierarchy had the most divergent response to the two stories.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This hierarchy, as well as the divergence of neural responses observed here, is additionally consistent with previously proposed linguistic hierarchies: low-level regions (A1+) represent phonemes (32,33), syllables (34), and pseudowords (35), while medium-level regions (areas along A1+ to STS) represent sentences (36,37). At the top of the hierarchy, high-level regions (bilateral TPJ, precuneus, and medial prefrontal cortex) can integrate words and sentences into a meaningful, coherent whole narrative (5,15,(38)(39)(40). We found that the regions at the top of the hierarchy had the most divergent response to the two stories.…”
Section: Discussionsupporting
confidence: 90%
“…It was previously suggested that this network of areas supports multimodal conceptual representation by integrating information from lower level modality-specific areas (11)(12)(13)(14)(15). However, the semantic models used in previous work (9)(10)(11)(12)(13)(14)(15) do not model the relationship between words over time. In real-life situations, the context of words can substantially influence their interpretation, and thereby their representation in the cortex.…”
mentioning
confidence: 98%
“…It may be the case that effects in these languagerelated regions are due to these processes. Previous research points to a role for the posterior temporal lobe in working memory and cognitive control (Hickok et al, 2003;Glaser et al, 2013) and the angular gyrus in semantic processing (Binder et al, 2009;Price et al, 2015), consistent with this speculation.…”
Section: Whole-brain Contrasts Of Complexity and Structuresupporting
confidence: 67%
“…S12). Thus, mathematical expertise enables the left angular gyrus, which is engaged in sentence-level semantic integration (35,36), to extend this function to mathematical statements. Importantly, this contribution is only transient, restricted to the sentence comprehension period, because this area was deactivated during mathematical reflection.…”
Section: Resultsmentioning
confidence: 99%